Great world religions Christianity - Johnson, Luke Timothy (Teaching Co., 2003)
Consists of twelve 30-min. lectures that provide an overview of Christianity. Explains why the central figures, elements, and creeds of Christianity give Christianity its distinctive character. Covers Christianity's birth and expansion across the Mediterranean world, the development of its doctrine, its assertion that Jesus was both a man and God, its transformation upon becoming Rome's imperial religion, its many and deep connections to Western culture, and the tensions in Christianity today.